Surveying in the Falkland Islands Dependencies - Stephenson, A. (Polar Record, 1951)
Summary An account of surveying in the Falkland Islands Dependencies could be treated as just another description of surveying in one of the outlying parts of the Empire. There is one major difference in comparison with other Colonies, however, which affects the whole outlook and conduct of the survey. This is that in the part of the Dependencies with which we are concerned, namely Graham Land and the Islands to the north, there is no permanent human habitation and no regular means of communication. I must refer briefly to the historical background of these surveys and the reason for their commission, especially the latter, as without a full understanding of the need and future use of a survey one cannot examine critically the methods used. Next I shall describe the methods of survey that have been used, which will inevitably entail describing the type of country and various difficulties peculiar to the polar regions. A summary of the accomplishments up to date will be very brief, as these are shown in the maps that have been published by the Directorate of Colonial Surveys and some of which will be on exhibition. Finally I shall consider some proposals for future surveys in this territory.